'Faith and work for King and Country!' Nationalization and covert Romanianization through the youth organization Straja Țării (1934–1940). Issue 4 (8th August 2021) - Filipovici, Anca
ABSTRACT: This study investigates the youth organization Straja Țării, created by King Carol II of Romania in the second interwar decade. The research will consider two levels of analyses: the organizational and ideological dimensions of Straja Țării within the national project of unification (1); the relation of the Jewish youth to Straja Țării (2). Although Straja included youngsters from ages 7 to 18, I will focus mainly on adolescents (above the age of 14), because they were a distinct instrumental group for radical political movements. The paper's main argument is that by being packed in the formula of nation-building and strengthening, Straja Țării was rather an ineffective organization which served as a tool to consolidate the king's power at both the internal and external level. In relation to ethnic minorities, Straja oscillated between recklessness, assimilation, and rejection, lacking any mechanism for integrating non-Romanians.